Malayan pit viper envenomation and treatment in Thailand - Thunyaporn Tangtrongchitr (2022)
Introduction: The Malayan pit viper (MPV; Calloselasma rhodostoma) is a hematotoxic snake found in all regions of Thailand and many countries in Southeast Asia. Treatment of MPV envenomation varies among facilities due to their capabilities. Materials and Methods: This study was a retrospective review of patients with MPV envenomation who were reported to the Ramathibodi Poison Center from 1 July 2016 to 30 June 2018. Results: Of the 167 patients (median age, 40.5 years; range, 1.3–87.0 years) bitten by an MPV, the most common bite site was the foot (29.3%). Most patients reached the hospital within 1 hour of being bitten. One-hundred fifty-six patients (93.4%) had local effects from envenomation; 17 patients (10.2%) had severe local complications including necrotizing fasciitis (3.0%) and compartment syndrome (7.2%). Systemic effects such as hemorrhage and abnormal hemostasis occurred in 147 patients (88.0%). Additional effects included abnormal venous clotting time in 123 patients (73.7%), unclotted 20-minute whole blood clotting time in 57 patients (34.1%), low platelet counts (<50,000/µL) in 29 patients (17.4%), prolonged international normalized ratio (>1.2) in 51 patients (30.5%), and systemic bleeding in 14 patients (8.4%). The median onset of bleeding disorder was 6 hours. Monitoring for 24, 48, and 49 hours after bite enabled detection of systemic effects in 94.2%, 99.3%, and 100.0%, respectively. Three hundred fifteen courses of antivenin were administered to 144 patients (86.2%). All the patients who received antivenin recovered from bleeding disorder. Only 7.0% of antivenin doses were administered without Thai Red Cross indications. Allergic reactions from antivenin occurred in 34.7% of the 144 patients. One hundred thirty patients (77.8%) received antibiotics, and 32 patients (19.2%) required surgical management, including debridement and fasciotomy. Conclusion: MPV envenomation results in local and systemic effects. Most systemic effects were abnormal clotting test results. Most patients reported onset of bleeding disorder within 48 hours.